EXPERIMENTAL APPLICATION OF THE METHOD OF FOCAL OBJECTS IN DESIGN EDUCATION - Angelova, Desislava (Innovation in Woodworking Industry and Engineering design, 2021)
This article discusses the practical application of the Method of Focal Objects in the learning process of students in the Engineering Design (Interior and Furniture Design) Program at the University of Forestry, Sofia, Bulgaria. The experiment has been conducted in studied course Innovative and Strategic Design with the students of the first course from the Master Degree Program. The experiment's main objective is to examine what influence the Method has on students' creativity. The methodology of the experimental conducting of the Method and the way of work have been described. Based on the obtained results, analyses have been made for the Method's application in students' learning process to develop their non-standard and analytical thinking.